An Evaluation of the Impact of a Structured Teaching Program on Staff Nurses' Knowledge of Low Back Pain Prevention in Intensive Care Units at Selected Hospitals in Bangalore - Munmun Mukherjee (International Journal of Orthopedic Nursing and Practices, 2024)
The study aimed to assess the knowledge of ICU nurses concerning the prevention of low back pain (LBP), determine the effectiveness of a structured teaching program (STP) in improving their knowledge, and examine the relationship between pre-test knowledge levels and various demographic factors. A pre-experimental research design was utilized, featuring a one-group pre-test and post-test method. The study employed non-probability convenience sampling to recruit 60 ICU nurses for participation. Data were collected using a structured knowledge questionnaire, which included two sections: socio-demographic data and knowledge on LBP prevention. Descriptive and inferential statistics, including frequencies, percentages, mean, standard deviation, chi-square, and ‘t’ tests, were used for data analysis. The majority of participants (35%) were in the 20–25 age group, with 68.33% being female and 45% identifying as Christian. Most nurses (43.33%) had 1–5 years of experience, and 78.33% held staff nurse positions. A significant percentage (38.33%) had a B.Sc. in Nursing, and 85% came from nuclear families. In terms of working hours, all nurses worked 6–8 hours daily, with 80% receiving information about LBP prevention from health personnel. The pre-test revealed that 60% of nurses had moderate knowledge of LBP prevention. Following the STP, 75% of the participants demonstrated adequate knowledge, 25% showed moderate knowledge, and none had inadequate knowledge, reflecting a notable improvement. The chi-square test showed a significant association between pre-test knowledge and demographic variables such as staff designation, education, type of family, and information source. In conclusion, staff nurses initially had limited knowledge about LBP prevention, but the STP effectively improved their knowledge. This highlights the importance of targeted educational interventions in enhancing nurses' awareness of LBP prevention strategies.
Keywords: ICU nurses; demographic variables; low back pain (LBP); structured knowledge questionnaire; structured teaching program (STP)